Parasitological, Hematological, and Immunological Response of Experimentally Infected Sheep with Venezuelan Isolates of Trypanosoma evansi, Trypanosoma equiperdum, and Trypanosoma vivax - Nereida Parra-Gimenez; Armando Reyna-Bello (Journal of Parasitology Research)
There are three trypanosoma species of veterinary importance in South America: (1) Trypanosoma evansi, the causative agent of derrengadera mechanically transmitted by bloodsucking insects such as tabanids, (2) Trypanosoma vivax, also mechanically transmitted by some dipteras hematophages as tabanids and/or Stomoxys, and (3) T. equiperdum, a tissue parasite adapted to sexual transmission and the causative agent of dourine, a distinctive disease that affects only Equidae. In order to evaluate the parasitological, hematological, and serological response of sheep infected with T. vivax, T. evansi, and T. equiperdum, four female sheep were experimentally infected with Venezuelan trypanosome field isolates: two T. evansi of differing virulences, one T. equiperdum; one T. vivax. Parasitemia and clinical parameters such as hematocrit, red blood cell count, hemoglobin, and body temperature were measured. T. evansi caused a chronic disease with undulant parasitemia alternating with some cryptic periods of at least 54 days, with no clinical signs. T. equiperdum, never described as infectious to ruminants, also caused a chronic disease with low undulant parasitemia. T. vivax caused an acute infection with severe anemia showing a drop of more than 70% of the hematocrit value, high fever, and rapid deterioration of physical condition, for 36 days of infection. Indirect ELISAs using crude extracts of the three species of trypanosomes as antigens were performed for detection of anti-trypanosome antibodies in sheep sera. Cross-reaction was observed between the three parasite species. These results show that sheep are susceptible to the three-trypanosome species and suggest they can act as a reservoir when sheep are raised and managed with other important livestock such as cattle, horses, buffalos, or goats. These findings are especially interesting for T. equiperdum, a species that has not been reported as infective to sheep.